Country data on AMR in Türkiye in the context of community-acquired respiratory tract infections: links between antibiotic susceptibility, local and international antibiotic prescribing guidelines, access to medicine and clinical outcome. (6th September 2022) - Torumkuney, Didem; Aktas, Zerrin; Unal, Serhat; van Hasselt, James; Seyhun, Yalcin; Keles, Nergis
Abstract: Background: Antimicrobial resistance (AMR) is one of the biggest threats to global public health. Selection of resistant bacteria is driven by inappropriate use of antibiotics, amongst other factors. COVID-19 may have exacerbated AMR due to unnecessary antibiotic prescribing. Country-level knowledge is needed to understand options for action. Objectives: To review AMR in Türkiye and initiatives addressing it. Identifying any areas where more information is required will provide a call to action to minimize any further rise in AMR within Türkiye and to improve patient outcomes. Methods: National AMR initiatives, antibiotic use and prescribing, and availability of susceptibility data, particularly for the key community-acquired respiratory tract infection (CA-RTI) pathogens Streptococcus pneumoniae and Haemophilus influenzae, were identified. National and international antibiotic prescribing guidelines commonly used locally for specific CA-RTIs (community-acquired pneumonia, acute otitis media, acute bacterial rhinosinusitis) were also reviewed, plus local antibiotic availability. Insights from both a local clinician and local clinical microbiologist were sought to contextualize this information. Conclusions: Türkiye developed an antibiotic stewardship programme, The Rational Drug Use National Action Plan 2014–2017, prioritizing appropriate antibiotic prescription in the community. Public campaigns discouraging inappropriate antibiotic use were also initiated. Türkiye has a high level of antibiotic resistance and a high level of consumption, however, in 2015 over-the-counter antibiotic sales were prohibited, resulting in a declining trend in overall consumption. There is still a need for physician education on current developments in antibiotic use. Several ongoing global surveillance studies provide antibiotic susceptibility data in Türkiye. Clinicians in Türkiye use several country-specific guidelines for common CA-RTIs plus a range of international guidelines. A more standardized inclusive approach in developing local guidelines, using up-to-date surveillance data on isolates from community-acquired infections in Türkiye, could make guideline use more relevant for clinicians. This would pave the way for a higher level of appropriate antibiotic prescribing and improved adherence. This would, in turn, potentially limit AMR development and improve patient outcome.